2010
DOI: 10.1016/j.jmb.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mutational Analysis of Peptide Inhibition of the p53–MDM2/MDMX Interactions

Abstract: Inhibition of the interaction between the tumor suppressor protein p53 and its negative regulators MDM2 and MDMX is of great interest in cancer biology and drug design. We previously reported a potent duodecimal peptide inhibitor, termed PMI (TSFAEYWNLLSP), of the p53-MDM2 and -MDMX interactions. PMI competes with p53 for MDM2 and MDMX binding at an affinity roughly two orders of magnitude higher than that of 17–28p53 (ETFSDLWKLLPE) of the same length; both peptides adopt nearly identical α-helical conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
180
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(198 citation statements)
references
References 58 publications
(102 reference statements)
17
180
1
Order By: Relevance
“…Uniformly 15 N-labeled or 15 N-and 13 C-labeled and unlabeled samples of WT and mutant versions of human p53TAD (residues 1-73) were prepared as previously described 12 . Samples of human Mdm2, corresponding to residues 17-125, were expressed using pGEX-6p-2 vectors in BL21(DE3) cells grown in M9 medium.…”
Section: Protein Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniformly 15 N-labeled or 15 N-and 13 C-labeled and unlabeled samples of WT and mutant versions of human p53TAD (residues 1-73) were prepared as previously described 12 . Samples of human Mdm2, corresponding to residues 17-125, were expressed using pGEX-6p-2 vectors in BL21(DE3) cells grown in M9 medium.…”
Section: Protein Purificationmentioning
confidence: 99%
“…2b). p53TAD and p53TAD P12A P13A bound to Mdm2 with similar affinities, whereas p53TAD P27A and p53TAD 3xA displayed approximately tenfold reductions in their dissociation constants [15][16][17] (Fig. 1c and Supplementary Fig.…”
mentioning
confidence: 99%
“…The up-regulation of miRNA-509-5p in HGC-27 cells could inhibit MDM2 expression, thus inhibiting cell proliferation, invasion, and migration. Some studies reported that MDM2 could work as a drug target for prostate cancer gene therapy, as the degradation of MDM2 could elevate intracellular p53 levels and potentiate p53 restrictive effects during the G1/S and G2/M phases, arresting cells at the G1/G2 phase and inducing apoptosis (Yin et al, 2003;Li et al, 2010). However, the exact underlying mechanism of regulation of MDM2 expression by miRNA-509-5p could not be elucidated and is the main limitation of the present study.…”
Section: Discussionmentioning
confidence: 80%
“…1) reveals that there are 2 putative sites for phosphorylation that lie within the p53 binding region: Thr18 and Ser20. The suggestion that phosphorylation of these sites destabilizes p53-MDM2 interaction is supported by alanine mutagenesis experiments 23 and computer simulations. 18,24,39,40 The physical rationale for the destabilization of binding is usually ascribed to thermodynamic effects 18 however, kinetic effects have not been studied in either experimental or simulation studies.…”
Section: Resultsmentioning
confidence: 88%
“…Phosphorylation of Thr18 was shown to weaken p53 MDM2 binding by approximately one order of magnitude 19,22 and the Thr18Ala mutation was found to reduce the binding affinity of p53 to MDM2 by roughly a factor of 3. 23 Computational models, partly validated by experiments, suggested that the effect of phosphorylation was attributed to enhancing elecrostatic repulsion in the region where Thr18 docks by placing the negatively charged phosphorylated Thr18 near anionic regions of the MDM2 surface. 18,24 Phosphorylation of Ser20, however, was found to be sufficient to disrupt the p53-MDM2 interaction.…”
Section: Introductionmentioning
confidence: 98%